Introduction of a new software package in teaching Design Methodology for material selection - Pramanik, Alokesh; Islam, Mohammad Nazrul (International Journal of Information and Education Technology, 2015)
Material selection is an integral part of engineering design. As such, this topic is included in most advanced engineering design units in the Bachelor of Mechanical Engineering. However, students often find this topic difficult and confusing due to the lack of overall knowledge required for the task. This paper describes the introduction of a new software package in a design methodology unit for material selection that provides additional knowledge and hands-on experience to students, which can be applied in their professional lives. The software package introduced three forms of education delivery: lecture, tutorial, and assignment activities. It was found that the introduction of the CES EduPack software package for material and process selection significantly improved students’ learning.